Consenso e sanção: uma teoria discursiva para um processo penal íntegro e democrático - Sousa Júnior, Eliezer Siqueira de (2019)
Conflict is inherent in social life. As a demonstration of force, power or dominance upon the other person, it has been shown that human relations are not immune to the daily life discord and tensions. It´s impossible to solve all human questions through confrontation, due to the financial, emotional and vitality expenses that everyday issues impose. Thus, consensus emerge s as a solution to be persecuted in society, as a more practical and effective way to solve those tensions. It should be highlighted that i n a world focused on gain and success, characteristic traits inserted in our daily life by the capitalist ideology, t alking about consensus may seem illogical. However, it must be pointed out that the development of the humanity only ocurred because of communication, understanding and language. If on the one hand it can be affirmed that the society develops through the c ommunicative process, the same can’t be verified with the public law system, especially the criminal court, that has traditionally distanced itself from the dialogical procedure, embracing various monological moments. Dialogue, as a tool of modern civiliza tion, must gain space in procedures in which it wasn´t considered, so that it can no longer be embodied in juridical dogmas that are not supported by the present. For this reason, the public interest must be attended to with the society participation, dire ctly and indirectly, for the purposes for which it is intended. Consensus must be progressively pursued to satisfy and legitimize both institutions’ and individuals’ choices. In criminal process, state paternalism, rooted in the idea that the State, throug h the judiciary, has to decide criminal law violations to guarantee the “jus puniendi” exercise with the use of unique procedures for a variety of conducts and legal assets. This practice should be replaced to more rational forms that take into account the nature of criminal offence, the damage suffered by the victims of harmful conduct, the author’s right guarantee in criminal act, the lowest burden on society, among other relevant factors. In this way, criminal procedure must continuously give way to stim ulate a greater participation of the citizens involved in the criminal procedure to legitimize and better address the problems of this sensitive area, with appropriate State intervention and effective satisfaction of social those.